Assessment of Radon Concentrations in Marine Biota of the Iraqi Marine Environment - Munaf Qasim Jaber; Muhammed Faris Abbas (Marine Science Department Diponegoro University, 2026)
In this study, samples were collected from three areas of the Iraqi marine environment, where fish are caught to be marketed to local markets for use as food. The study area includes coral reef, Khor Abdallah, as well as Um Qaser Port. Using the closed cylinder technique with Solid State Nuclear Track Detector (SSNTDs) CR-39. The concentration of Radon-222 was measured, as well as the radium equivalent, in addition to the emission per unit area and the emission per unit mass. The results are arranged by region as follows: In the Coral Reef, the lowest value was found in the bivalve Corbicula and was 14.01±4.68 Bq.m-3, while the highest concentration of Radon-222 gas isotope value was in the shrimps; 69.52±19.33 Bq.m-3 , with an average value of 28.69±9.1 Bq.m-3. In Kohr Abdallah, the lowest concentration of Radon-222 gas isotope value was found in the Laevicardium sample, it was 16 Bq.m-3 , while the highest value was in the Shrimps too, which was 61 Bq.m-3. This value is close to the value of the shrimps in the coral reef area, with the average value 37±11.2 Bq.m-3. In the Um Qaser area, the lowest concentration of Radon-222 9.93±3.76 Bq.m-3 was found in Cerithium scabridum whereas the highest value was 29.03±8.84 Bq.m-3 and found in the Anemones sample. Based on the measurements taken in this study, in which the concentration of radioactive Radon-222 isotope was calculated, it appears that the measured concentration values are within the acceptable range, and therefore the use of these samples does not pose a risk if used.